Emergência do calazar em município da pré-amazônia maranhense: aspectos epidemiológicos e clínicos - MARTINS, Clara Claryannah de Souza (2021)
Introduction: The municipality of Buriticupu started along with the Agricultural Colonization project which was created by the Law 3,230/1971. It is located in the west of Maranhão and belongs to the Pindaré micro-region. It has a low socioeconomic level with a Human Development Index (HDI) of 0.556. In 2008, had the Local Health System vulnerable by the emergence of visceral leishmaniasis (calazar) hitherto not registered in its territory. Objectives: to characterize the demographic, epidemiological and clinical profile of visceral leishmaniasis; to describe the structure of the local health system; to identify the disease vector in the municipality. Casuistic and Methods: a descriptive study was carried out covering the period from 2008 to 2018. Secondary data were collected through the Notifiable Diseases Information System (SINAN) and through a questionnaire applied to the patients' family members during home visits. Data health structure was obtained in documents from the health department and in the testimonies of the professionals. The search for Leishmania infantum chagasi vectors was carried out in peridomiciliar and intradomiciliar captures, using CDC light traps. Data obtained were organized in Microsoft Excel 2019 spreadsheets, consolidated and presented by methods of descriptive statistics, using Biostat 5.0 program. Findings: 69 cases of visceral leishmaniasis were confirmed, with an increase in the case record, with an average of 3 cases from 2008 to 2010, and 10 cases from 2016 to 2018. The highest proportion of cases (87.7%) occurred in the urban area; 57.8% were under 10 years old and 60.8% were male. Fever (96.4%), pallor (85.7%), abdominal protrusion (62.5%), were the most frequent clinical manifestations that motivated. Considering all patients, 55% had laboratory confirmation (spinal puncture or serological examination); 21.7% were considered clinical-epidemiological criteria and 23.2% of the forms had no information. The pentavalent antimonial was used to treat 53.6%, followed by amphotericin B deoxycholate (11.6%). The overall lethality was 5.8%, but for children under 10 years old, it was 7.5%. In the vector captures among 824 species of Phlebotomines, Lutzomyia longipalpis was identified in 821 specimens. 48 (5.8%) were female. From the statistical point of view, the expected and observed frequencies in relation to gender were compared. The Chi-square statistic value of 3.00 is not significant at 5%, that is, there is no evidence that gender has a relationship of dependence with age group. Similarly, the expected and observed frequencies were compared in relation to the origin of the cases. The value of the Chi-square 0.99 statistic is not significant at 5%, there is no evidence that the origin of the cases has a relationship of dependence with age group. The expected and observed frequencies were also compared in relation to the outcome. The value of the Chi-square statistic 1.63 is not significant at 5%, i.e. no evidence that the origin of the cases has a relationship of dependence with age group. Conclusions: visceral leishmaniasis reached the municipality as an emergent disease. Since 2018, it was considered an endemic and highly transmitted disese.